The value relevance of environmental emissions - Melinda Lydia Nelwan (Universitas Hayam Wuruk Perbanas, 2016)
This study examines whether environmental performance has value relevance by investigating the relations between environmental emissions and stock prices for the U.S. public companies. The previous studies argued that the conjectured relations between accounting performance measures and environmental performance do not have a strong theoretical basis, and the modeling of relations between market per-formance measures and environmental performance do not adequately consider the relevance of accounting performance to market value. Therefore, this study examines whether publicly reported environmental emissions provide incremental information to accounting earnings in pricing companies stocks. It is done among the complete set of industries covered by Toxics Release Inventory (TRI) reporting for the period 2007 to 2010. Using Ohlson model but modified to include different types of emis-sions, it is found that ground emissions (underground injection and land emissions) are value relevant but other emission types (air and water and transferred-out emis-sions) appear to not provide incremental information in the valuation model. The result in this study raise concerns that different types of emissions are assessed differently by the market, confirming that studies should not aggregate such measures.